New testament apocrypha: more noncanonical scriptures / volume 2 - Burke, Tony (New Testament Apocrypha more noncanonical scriptures, 2020)
Volume 2 : --I. Gospels and Related Traditions of New Testament Figures : --The adoration of the Magi /Adam Carter Bremer-McCollum --The rebellion of Dimas /Mark G. Bilby --A homily on the life of Jesus and his love for the apostles /Timothy Pettipiece --A homily on the passion and resurrection /Dylan M. Burns --The book of Bartholomew /Christian H. Bull andAlexandros Tsakos --The healing of Tiberius /Zbigniew Izydorczyk --The legend of the Holy Rood tree /Stephen C. E. Hopkins --The story of Joseph of Arimathea /Bradley N. Rice --A homily on the building of the first Church of the Virgin /Paul C. Dilley --The life of Judas /Brandow W. Hawk andMari Mamyan --The life of Mary Magdalene /Christine Luckritz Marquis --II. Apocryphal Acts and Related Traditions : --The acts of Nereus and Achilleus /Richard I. Pervo --The act of Peter in Azotus /Cambry G. Pardee --The exhortation of Peter /J. Edward Walters --The travels of Peter /J. Edward Walters --The history of Philip /Robert A. Kitchen --The acts of Thomas and his wonderworking skin /Jonathan D. Holste andJanet E. Spittler --III. Epistles : --The epistle of Pelagia /Slavomír Čéplö --IV. Apocalypses : --The dialogue of the revealer and John /Philip L. Tite --1 apocryphal apocalypse of John /Rick Brannan --2 apocryphal apocalypse of John /Rebecca Draughon,Jeannie Sellick, andJanet E. Spittler --3 apocryphal apocalypse of John /Chance E. Bonar,Tony Burke, and Slavomír Čéplö --The questions of James to John /Kathleen Gibbons andTony Burke --The mysteries of John /Hugo Lundhaug andLloyd Abercrombie --The investiture of the Archangel Michael /Hugo Lundhaug ;Appendix :John of Parallos,Homily against heretical books /Christian H. Bull andLance Jenott --The investiture of the Archangel Gabriel /Lance Jenott --The apocalypse of Thomas /Matthias Geigenfeind --V. Church Orders : --The teaching of the apostles /Witold Witakowski